Minas Gerais e Belo Horizonte: inserção no Mercosul e mercocidades - Braga, Hélcio Queiroz (2010)
This Master Degree´s Dissertation deals with the theme of the international relations of sub-national entities, as well as the network formation that links political and administrative actions of state sub-national entities. Thus the focus was the analyses of Belo Horizonte´s international insertion, regarding the approximation and occupation of this political space. In this process two aspects are analyzed: the first, regarding the set of institutional actions taken by the municipal and state governments, with their progress, stalemates and perspectives. The second, regarding the municipal government´s political options for this insertion, like the protocols of brotherhood with cities of different countries and the joining of various networks that congregate cities for the exchange of good and innovative practices in the political direction of cities